Dimensi Experiential Marketing Terhadap Visitor Satisfaction Pada Wisata Malang Night Paradise - Tri Sugiarti Ramadhan; Nanik Wahyuningtiyas (Jurnal Ecogen, 2021)
The purpose of this study was to determine the effect of the Dimension Experiential Marketing (Y) on visitor satisfaction at Malang Night Paradise. The population taken in this study were visitors who came to visit Malang Night Paradise Tourism. This research includes visitor satisfaction variable as dependent variable and dimension experiential marketing variable as independent variable consisting of Sense(X1), Feel(X2), Think(X3), Act(X4) and Relate(X5). in this study using accidental sampling technique as many as 96 respondents. Simultaneously, the Experiential Marketing variable has a significant effect on visitor satisfaction of Malang Night Paradise. Then partially there are two variables that do not have a significant effect, namely the taste variable and the related variable. Meanwhile, the other three variables, namely feel (X2), think (X3), and act (X4) have a significant effect on the visitor satisfaction variable (Y) at Malang Night Paradise. With an R2 value of 63.7%, while 36.3% is influenced by other factors that can affect visitor satisfaction.